2021
DOI: 10.3389/fsoc.2021.631537
|View full text |Cite
|
Sign up to set email alerts
|

How do Individuals Form Their Motivations to Expatriate? A Review and Future Research Agenda

Abstract: For two decades, individual motivations to expatriate have received substantial attention in the expatriation literature examining self-initiated and assigned expatriation. Recently, however, this literature has changed direction, demonstrating that prior to forming their actual motivations, individuals undergo a process wherein they actively form those motivations. No review has yet unraveled this motivation process, and this systematic literature review fills this gap. Using the Rubicon Action model that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Among the UK's foreign-born population, expatriates are an important part of it. Although usually motivated by work, expatriates are also commonly driven by personal goals such as experiencing a new culture (Arifa et al, 2021). The UK has historically been an attractive country to expatriates coming from a variety of countries.…”
Section: The Uk's Hostile Environment Policy and Brexitmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the UK's foreign-born population, expatriates are an important part of it. Although usually motivated by work, expatriates are also commonly driven by personal goals such as experiencing a new culture (Arifa et al, 2021). The UK has historically been an attractive country to expatriates coming from a variety of countries.…”
Section: The Uk's Hostile Environment Policy and Brexitmentioning
confidence: 99%
“…In the three example stories discussed in this chapter, the expatriates had strong personal motivations to expatriate, such as experiencing a different culture. This makes their involvement with their chosen host society and culture even more important, and consequently the importance of feeling welcomed (Arifa et al, 2021). However, considering those who are negatively affected by these expatriate threats -such as those in this chapter's example stories -it is important to raise awareness of this potential obstacle in an expatriate's life.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Previous research has identified various motivations for expatriation (e.g. financial, family and adventure) (Arifa et al ., 2021; Brewster et al ., 2021; Muir et al ., 2014; Nolan and Morley, 2014; Tharenou, 2013). A closely related inquiry addressed the motivations from the perspective of motivational theories, such as the Self-Determination Theory (SDT) (Deci and Ryan, 1980, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…, 2012), but always with the overall perspective that there will be a return to the home country. Researchers have examined SIEs from a number of different angles, including characteristics (Myers and Pringle, 2005), motivation (Thorn, 2009; Arifa et al. , 2021; Farcas and Goncalves, 2017) and gender (Doherty and Thorn, 2014; Haak-Saheem et al.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the SIE is viewed as an opportunity to experience living and working in a different country (Shaffer et al, 2012), but always with the overall perspective that there will be a return to the home country. Researchers have examined SIEs from a number of different angles, including characteristics (Myers and Pringle, 2005), motivation (Thorn, 2009;Arifa et al, 2021;Farcas and Goncalves, 2017) and gender (Doherty and Thorn, 2014;Haak-Saheem et al, 2022). SIEs have been studied from and in specific geographic locations (Furusawa and Brewster, 2018;Pinto and Ara ujo, 2016) and by occupations (Richardson, 2012;Selmer and Lauring, 2010).…”
Section: Introductionmentioning
confidence: 99%